Crosstalk between the Warburg effect, redox regulation and autophagy induction in tumourigenesis - Mokgadi Violet Gwangwa; Anna Margaretha Joubert; Michelle Helen Visagie (Cellular & Molecular Biology Letters, 2018)
Abstract Tumourigenic tissue uses modified metabolic signalling pathways in order to support hyperproliferation and survival. Cancer-associated aerobic glycolysis resulting in lactic acid production was described nearly 100 years ago. Furthermore, increased reactive oxygen species (ROS) and lactate quantities increase metabolic, survival and proliferation signalling, resulting in increased tumourigenesis. In order to maintain redox balance, the cell possesses innate antioxidant defence systems such as superoxide dismutase, catalase and glutathione. Several stimuli including cells deprived of nutrients or failure of antioxidant systems result in oxidative stress and cell death induction. Among the cell death machinery is autophagy, a compensatory mechanism whereby energy is produced from damaged and/or redundant organelles and proteins, which prevents the accumulation of waste products, thereby maintaining homeostasis. Furthermore, autophagy is maintained by several pathways including phosphoinositol 3 kinases, the mitogen-activated protein kinase family, hypoxia-inducible factor, avian myelocytomatosis viral oncogene homolog and protein kinase receptor-like endoplasmic reticulum kinase. The persistent potential of cancer metabolism, redox regulation and the crosstalk with autophagy in scientific investigation pertains to its ability to uncover essential aspects of tumourigenic transformation. This may result in clinical translational possibilities to exploit tumourigenic oxidative status and autophagy to advance our capabilities to diagnose, monitor and treat cancer.